The Role of State Context in Promoting Service Coordination in Maternal, Infant, and Early Childhood Home Visiting Programs. Issue 1 (January 2020) - West, Allison; Duggan, Anne K.; Gruss, Kelsey; Minkovitz, Cynthia S.
Abstract : Context: The federal Maternal, Infant, and Early Childhood Home Visiting (MIECHV) program provides funding to states to promote health and development of at-risk expectant families and families with young children. MIECHV programs are required to coordinate services within a larger system of care; yet, little is known about state-level factors that support coordination. Objective: This study examined state-level supports and barriers for coordination of home visiting with other entities within the early childhood system of care. Methods: A Web-based survey was distributed in 2016 via e-mail to MIECHV administrators in all 50 states, 5 US territories, and the District of Columbia. The survey elicited information on 5 domains shown by theory and prior research to support coordination: MIECHV leadership, state leadership, shared goals across sectors, data systems, and finance. Respondents also rated their perceptions of state-level coordination. Results: Forty-two (75%) of the MIECHV administrators participated in the survey. States and territories varied widely within and across the 5 domains of support for coordination. MIECHV leadership was an area of relative strength, whereas data systems and finance showed the most room for improvement. State leadership and shared goals were associated with stronger perceptions of state-level coordination. Conclusions: The findings indicate opportunities for shared learning among states to enhance coordination infrastructure. Such efforts should include multiple stakeholder perspectives and consideration of local and organizational contexts. This work could be facilitated using the service coordination toolkit developed as part of this project.